Water management and environmental problems of the Ob basin: current state and forecast until  - Alexandr V. Puzanov; Dmitry M. Bezmaternykh; Nadezhda I. Yermolaeva; Alexandr T. Zinovyev; Evgeniya D. Kosheleva; Bella A. Krasnoyarova; Olga V. Lovtskaya; Tatyana S. Papina; Irina D. Rybkina; Dmitry N. Troshkin; Sofia N. Sharabarina; Lyubov V. Yanygina (Водное хозяйство России: проблемы, технологии, управление)
In the long-term dynamics (1995-2017) the volumes of water consumption in the regions of the Ob-Irtysh basin are falling, as well as in the whole of the country. The current period (2013-2020) is characterized by opposite trends: the growth in water consumption is almost 30% compared to 2013.